If It Takes a Village to Foster Innovation, Success Depends on the Neighbors: The Effects of Global and Ego Networks on New Product Launches. (June 2016) - Fang, Eric (Er); Lee, Jongkuk; Palmatier, Robert; Han, Shunping
Launching breakthrough and incremental new products is vital to firm performance; it also resonates with both ego (i.e., directly connected partners) and global (i.e., interconnected ties in an industry) network perspectives. Prior research has listed several ego network– and global network–level factors that affect innovations, but this study goes a step further, to reveal the interactions of these factors as critical product launch mechanisms. An analysis of alliance networks in the consumer packaged goods industry from 1990 to 2010 shows that a central position in a global network represents a double-edged sword: it improves a firm's incremental new product launches but harms its breakthrough new product launches. Furthermore, a firm's ego network (manifested as density and diversity) and R&D capability enable it to leverage its global network position by enhancing the benefits for incremental new products and mitigating its hazards for breakthrough new products. This study's findings thus offer new insights into the role of ego and global networks in facilitating or hindering new product launches.